Labor Market Flexibility: Advantages for Workforce or Threat? - Alih Aji Nugroho (Indonesian Association for Public Administration, 2018)
Labor Market Flexibility (LMF) which is supported by the law of supply and demand are considered capable of creating an eﬃcient labor market. As well as apprenticeship programs were considered to improve the quality of the labor force which can suppress the number of unemployed. Whether the application of LMF can be a positive impact like as imagined by its proponents? This is the result of research that seeks to see the dynamics of industrial relations faced by the workforce under the LMF system and dismantle the neoliberal project of the apprenticeship system. The study was conducted during September-November 2016 in the industrial area of Bekasi. The study used a descriptive qualitative approach. Collecting data through participatory research or live in. Searchable data sources using methods of a snowball eﬀect. In the end, this study involved seven trade unions, six companies, two foundations labor brokers, three government agencies, 35 workers (10 contract workers, 10 workers outsourcing, and 15 workers apprenticeship) and three labor activists. The result is the implementation of contract system and outsourcing many violate the rules. In the industrial area of Bekasi composition flexible workforce of more than 50% of the total workforce. And under the LMF system occurs bureaucratization in industrial relations. In addition, LMF policy does not reduce unemployment but only rotate unemployment. and the apprenticeship system is expected to increase human resources in the labor force application only used by the owners of capital to get cheap labor.